INTEGRATING BANYUWANGI CULTURE INTO JUNIOR HIGH SCHOOL ENGLISH TEACHING - Putri Balqis; Dewi Ratu Bilqis; Iva Novita; S. Ahmad Marjuki Mustofa; Dana Yudha Kristiawan (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
English instruction becomes more contextually meaningful when learners can use the language to represent people, places, practices, and products that they already recognise. However, English as a foreign language materials frequently foreground distant or globally standardised contexts, while detailed classroom accounts of how local content is aligned with language objectives and communicative tasks remain limited in Banyuwangi. This exploratory qualitative classroom report examined how Banyuwangi cultural content was incorporated into two documented junior high school lessons, what patterns of student participation were observable, and what instructional challenges occurred. The available teaching-practicum archive comprised one Grade 7 lesson on traditional foods and one Grade 8 lesson on dances, festivals, tourist destinations, and cultural practices. Data consisted of descriptive observation notes and lesson documents, including visual prompts, vocabulary lists, sentence frames, and activity instructions. The materials were analysed through reflexive thematic analysis using a hybrid process that combined culturally relevant pedagogy with inductive coding. The records showed that local topics supplied accessible content for vocabulary, description, information exchange, presentation, and tourist-local role-play. Participation was most visible when learners had visual prompts, word banks, sentence frames, rehearsal, and clearly assigned roles. The records also documented pauses, pronunciation difficulty, limited vocabulary, reliance on prompts, brief Indonesian help-seeking, and unequal contribution. The report concludes that local culture can serve as meaningful language content when cultural relevance, explicit language targets, scaffolded practice, and communicative outcomes are deliberately aligned. Because the archive did not retain class-size, lessonduration, direct student-voice, or performance-gain data, the findings concern instructional feasibility and observable participation rather than motivation or proficiency improvement.